Economic Growth, Demography and Social Change in Nigeria: An ARDL Analysis - Shuaibu Mukhtar (International Journal of Economic, Finance and Business Statistics, 2023)
Nigeria is estimated to have over 200 million people, this make it necessary for Nigerian government to be very watchful of demographic transition. Effect of population on economic growth is relative. Nigeria found herself in between the two extreme positions, thus it needs to (very well) be mindful of how its population growth. This paper has tested two models that try to explain the relationship between social change, population growth and economic growth, using the econometric techniques of ARDL cointegration and Multiple regression analysis. It findings show that population growth affect economic growth in Nigeria; while birth rate affects economic growth positively, death rate affects economic growth negatively. It also shows that net migration, health expenditure and labour force affect economic growth. Population growth is affected by economic growth, labour force and health expenditure.